1998
DOI: 10.1093/genetics/149.3.1323
|View full text |Cite
|
Sign up to set email alerts
|

A New Marker for Mosaic Analysis in Caenorhabditis elegans Indicates a Fusion Between hyp6 and hyp7, Two Major Components of the Hypodermis

Abstract: A fusion of the sur-5 protein to the green fluorescent protein containing a nuclear localization signal is demonstrated as a marker for genetic mosaic analysis in the nematode Caenorhabditis elegans. Because of an extensive accumulation of bright fluorescence in many nuclei, normal growth plates, each containing hundreds of worms, can be rapidly screened with a dissecting microscope for rare mosaic individuals. As the marker can also be used to detect transgenic worms, the construction of strains for mosaic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…While it has been suggested that individual importins act as receptors for several different types of protein cargo, 47 we reasoned that AKIR-1 is likely involved in a more limited role. We therefore used a nuclear localized GFP transgenic reporter strain ( sur-5p::NLS-GFP ) 33 , 48 to investigate whether AKIR-1 affects nuclear import in general. As expected, RNAi against ima-3 markedly reduced the GFP signal in intestinal nuclei, but akir-1 RNAi had no effect on the nuclear localization of the GFP reporter suggesting a more specific role for akir-1 in nuclear import than for importins ( Figure 7 E).…”
Section: Resultsmentioning
confidence: 99%
“…While it has been suggested that individual importins act as receptors for several different types of protein cargo, 47 we reasoned that AKIR-1 is likely involved in a more limited role. We therefore used a nuclear localized GFP transgenic reporter strain ( sur-5p::NLS-GFP ) 33 , 48 to investigate whether AKIR-1 affects nuclear import in general. As expected, RNAi against ima-3 markedly reduced the GFP signal in intestinal nuclei, but akir-1 RNAi had no effect on the nuclear localization of the GFP reporter suggesting a more specific role for akir-1 in nuclear import than for importins ( Figure 7 E).…”
Section: Resultsmentioning
confidence: 99%
“…Whilst it has been suggested that individual importins act as receptors for several different types of protein cargo (Kimura et al, 2017), we reasoned that AKIR-1 is likely involved in a more limited role. We therefore used a nuclear localized GFP transgenic reporter strain ( sur-5p::NLS-GFP ) (Yochem et al, 1998; Mikkonen et al, 2017) to investigate whether AKIR-1 affects nuclear import in general. As expected, RNAi against ima-3 markedly reduced the GFP signal in intestinal nuclei, but akir-1 RNAi had no effect on the nuclear localization of the GFP reporter suggesting a more specific role for akir-1 in nuclear import than for importins (Figure 9E).…”
Section: Resultsmentioning
confidence: 99%
“…Incorporation at the UAGA codon thus results in production of a GFP::mCherry fusion protein that localizes to the cell nucleus due to the C-terminal NLS. Expression of the protein coding genes was driven by the ubiquitous sur-5p promoter ( 34 ). To construct strains, we used a genetic background containing a deletion in the smg-6 gene, knocking out the nonsense mediated decay machinery ( 35 ).…”
Section: Resultsmentioning
confidence: 99%